Phase II trial of bevacizumab + cetuximab + cisplatin with concurrent intensity‐modulated radiation therapy for patients with stage III/IVB head and neck squamous cell carcinoma. (6th July 2015) - Fury, Matthew G.; Xiao, Han; Sherman, Eric J.; Baxi, Shrujal; Smith–Marrone, Stephanie; Schupak, Karen; Gewanter, Richard; Gelblum, Daphna; Haque, Sofia; Schoder, Heiko; Shah, Jatin P.; Katabi, Nora; et al.
Abstract: Background: The purpose of this study was to evaluate the efficacy and tolerability of the addition of 2 monoclonal antibodies, bevacizumab and cetuximab, to 2 cycles of high‐dose cisplatin administered concurrently with intensity‐modulated radiation therapy (IMRT) for head and neck squamous cell carcinoma (HNSCC). Methods: Patients with newly diagnosed stage III/IVB (M0) HNSCC received cetuximab (400 mg/m 2 loading dose, followed by 250 mg/m 2 weekly), bevacizumab (15 mg/kg, days 1 and 22), and cisplatin (50 mg/m 2, days 1, 2, 22, and 23) concurrently with IMRT (70 Gy). The primary endpoint was progression‐free survival (PFS). Secondary endpoints were overall survival (OS) and safety and tolerability. Results: Among 30 patients enrolled in this study, the primary tumor site was the oropharynx in 24 patients (p16 immunohistochemistry was positive in 17, negative in 1, and not done in 6 of the oropharyngeal tumors). Median age was 57 years (range, 38–77 years) and 27 patients had clinical stage IVA disease. All patients completed the full planned dose of radiation therapy. The most common ≥ grade 3 adverse events were lymphopenia, mucositis (functional), and dysphagia. With a median follow‐up of 33.8 months, 2‐year PFS was 88.5% (95% confidence interval [CI] = 68.1–96.1) and 2‐year OS was 92.8% (95% CI = 74.2–98.1). Conclusion: The addition of bevacizumab and cetuximab to 2 cycles of cisplatin, given concurrently with IMRT, was well‐tolerated and was associated with favorable efficacy outcomes in this patient population. © 2015 Wiley Periodicals, Inc. Head Neck 38: E566–E570, 2016